KEBIJAKAN PENGENDALIAN HARGA SULTAN ALAUDDIN KHALJI DI INDIA - Fadli Hudaya (Neraca, 2012)
The goals of this research are to find out and to explain what are the reasons that price control policy was introduced, how was the price control policy worked, what are the impacts, and the focus of the research is in time of the regime of Sultan Alauddin Khalji in India on 1290-1320 A. D. The research is individual life history in qualitative approach, it was did by historical analysis, it’s mean to investigate, to describe, and to examine the object of the research in his behavior, the researcher would systematizes, it was began by collecting of informations to analysis, to confirm, to serve for, and to conclude from it. The out put of the research explains that the reasons of Sultan Alauddin Khalji introduced the price control policy are to make safe his state in the condition of rebellions, the empty of the government treasury, the price of the essential goods was so high, the administrative machinery works ineffective and inefficient, and the invasion of Mongol, the solution of these problems were to brought the government authority back by the strengthening of his army, which it makes the state safe from the invasions of Mongol and the rebellions, and raises the law back. The strong army could be created in the economic condition of the state had been stronger before, and it could be created if the price of the necessaries of live had been cheap that be controlled by the policy. The policies were 5 regulations, they were fixing the price of the necessaries of life, founding the department to control the markets and it works in one control system to report directly to Sultan from three resources of the information, building up the royal granaries that managed by a department, serving the caravans to bring the commodities from peasants to royal granaries, and from it to the markets, incrising the output of agricultural commodities. The impacts of this policy in the political side are to increase of the state ability for enlarging of the territory, to make the state safe from the rebellions and the invasion of Mongol, in the economic side are, the life of state was in peace and comfort, the necessaries of life became cheaper, and in the sociological side are, the moral conditions of the society was exemplary that did not live with wine, prostitutes, and gambling. This price control policy maybe would be exemplary for the states in the other side in the world.